CULTURAL DIFFERENCES BETWEEN THE UK AND UZBEKISTAN - Ismoilova Marjona; Musajonova Naimaxon; Botirova Khakima (Ustozlar uchun, 2023)
Annotation: This article explores the notable differences in the cultures between the United Kingdom and Uzbekistan. It delves into various aspects such as family habits and traditions and this article compares the overall structure of culture in both countries.